A new species of Macrothrix (Crustacea, Branchiopoda, Macrothricidae) from the Neotropics with description of the marthae-group - Sousa, Francisco Diogo R. (2021)
Publications of the last three decades demonstrated the existence of some compact species groups within the Macrothrix Baird genus (Cladocera: Macrothricidae). Many species were included in hirsuticornis-group, laticornis-group, roseatriserialis-group and paulensis-group, but not in Macrothrix marthae group. It has a peculiar set of morphological traits not observed in any other species, so far. Studying material from Ribeira de Iguape River, Brazil, we found some individuals that resemble M. marthae, which represent a new species described herein. Macrothrix lourdesae sp. nov shares with M. marthae similar morphology of Inner Distal Lobe setae and the same modifications on the fourth and fifth limbs. The main difference between them is related to the number of setae in the exopodite of the third limb. Observing the high number of morphological traits shared, it is possible to indicate that M. lourdesae sp. nov and M. marthae form a separate species group within the genus.